2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.26856
|View full text |Cite
|
Sign up to set email alerts
|

Disruption in Large Classes during Active Learning Sessions

Abstract: Large class sizes are increasingly common in mechanical engineering undergraduate courses due to increased enrollments of undergraduate students with a disproportional investment to faculty numbers. Simultaneously, active learning is promoted to faculty members over traditional lectures due to published findings of improved student learning. Active learning typically involves a break in the lecture to allow for problem solving, discussion, or other activities. One common type of active learning in large classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This frustration with perceived disorganization was also reflected in the survey comments from older students, including that of the 20-year old student quoted above. They were more likely to find the active learning sessions, especially those which did not include problem-solving exercises, as "busy work" and unnecessary for their success in the class and may reflect differences in motivational factors and preferred learning environments noted by some researchers [32], [33]. The differences in gender are more puzzling and are contrary to what has been reported in studies of active learning implementation in other STEM courses [34], [35].…”
Section: ) Enjoyedmentioning
confidence: 80%
“…This frustration with perceived disorganization was also reflected in the survey comments from older students, including that of the 20-year old student quoted above. They were more likely to find the active learning sessions, especially those which did not include problem-solving exercises, as "busy work" and unnecessary for their success in the class and may reflect differences in motivational factors and preferred learning environments noted by some researchers [32], [33]. The differences in gender are more puzzling and are contrary to what has been reported in studies of active learning implementation in other STEM courses [34], [35].…”
Section: ) Enjoyedmentioning
confidence: 80%
“…Prince reports that students retain knowledge better when lectures are interspersed with brief periods of activity [15] . Simply adding the use of clickers during lecture classes is not perceived as active learning by students [24] . Butler says that using active learning breaks during lectures can help students retain the concepts being studied [25] .…”
Section: Why Active Learning?mentioning
confidence: 99%
“…The nine activities that will be covered in detail below are as follows: (1) Understanding Variables and Arrays with Paper Bags [2], (2) Branching and Looping Statements with Starburst Candies [2], (3) Loops with Music [3], (4) Arrays with Tissue Boxes, DVD Sets, Paper Plates, and other Household Goods [2], (5) Monsters Hate Chocolate: Learning Try/Catch Blocks [2], (6) General Class Structure with Bags, Boxes, and a Bin [2], (7) Dr. Doolittle's Vet Office: Learning Classes with Stuffed Animals [2], (8) Sorting Algorithms with Paper Bags [3], and (9) Recursion Introduction: Simple Tower of Hanoi with Colored Paper [3]. Key topics covered by these activities include: (1) variables, (2) arrays, (3) if statements, (4) loops, (5) Try/ Catch blocks, (6) Exceptions, (7) classes, (8) sort algorithms, and (9) recursion.…”
Section: Overview Of the Activitiesmentioning
confidence: 99%
“…Teaching lectures with hundreds of students in a large lecture hall comes with a variety of challenges. The addition of active learning into large classrooms has been shown to be highly effective overall [4] but it has been reported that is often less effective with freshman than senior courses [5] and comes with logistical issues [4]. The authors will be focusing on overcoming these logistical issues for activities designed for a smaller classroom.…”
Section: Introductionmentioning
confidence: 99%